Consider a finite sequence $x_i \in (0,1)$ for $i=1,\ldots, n$ and define $y_i=\dfrac{\Pi_{j=1}^n x_j }{x_i}$.

I solved this system for $x$ in terms of $y$ and got $$x_i=\dfrac{\left(\Pi_{j=1}^n y_j \right)^\frac{1}{n-1}}{y_i}.$$

Now pick some $m<n$. Is there a simple way of solving $(x_1,\ldots x_m, y_{m+1},\ldots, y_n)$ in terms of $(y_1,\ldots y_m, x_{m+1},\ldots, x_n)$?

If we take logs, this is a linear system. My only idea on how to solve is to write the system for $n=2,3$ and solve it by brute-force to see if some pattern emerges and if so, make a conjecture and prove it... But perhaps someone can easily see some clever trick I am missing. This is not homework. It is for some lemma I need in my paper.


Define $x_i'=x_i$ and $y_i'=\dfrac{y_i}{x_{m+1}\ldots x_n}$, for $i\leq m$. Notice that $y_i'=\dfrac{\prod_{i=1}^m x_i'}{x_i'}$.

Now use your second formula to write $x_i=x_i'(i\leq m)$ as a function of $y_i'$. Notice that $y_i'$ depends only on $y_1,\ldots,y_m,x_{m+1},\ldots ,x_n$.

Next, for $j>m$, notice that $y_j=\dfrac{\prod_{i=1}^m x_i'\prod_{i=m+1}^n x_i}{x_{j}}$. Remind that we know how to write $x_i'$ depending on $y_1,\ldots,y_m,x_{m+1},\ldots ,x_n.$ So you can write $y_j(j>m)$ depending on $y_1,\ldots,y_m,x_{m+1},\ldots ,x_n.$


Rewriting the equations in the linearized form, you can use a block decomposition

$$\left[ \begin{array}{ccc} A & B\\ C& D \end{array} \right] \left[ \begin{array}{ccc} x_0\\ x_1\end{array} \right]=\left[ \begin{array}{ccc} y_0\\ y_1\end{array} \right]$$

and solve for the vector sections that you want


Letting $O_{mk}$ be a rectangular matrix of all ones, we have

$$A=O_{mm}-I_m,$$ and $$A^{-1}=\frac1{m-1}O_{mm}-I_m.$$

Given the simple structure of the blocks, a closed formula is possible. Let us denote $X_1$ and $Y_0$ the sum of the components of $x_1$ and $y_0$. Then,

$$A^{-1}y_0=\frac{Y_0}{m-1}O_{m1}-y_0$$ $$A^{-1}Bx_1=(\frac1{m-1}O_{mm}-I_m)O_{m,n-m}x_1=(\frac1{m-1}O_{mm}-I_m)O_{m1}X_1=\frac{X_1}{m-1}O_{m1}$$ and $$x_0=\frac{Y_0-X_1}{m-1}O_{m1}-y_0.$$


$$y_1=O_{n-m,m}x_0+(O_{n-m,n-m}-I_{n-m})x_1\\ =(m\frac{Y_0-X_1}{m-1}-Y_0)O_{n-m,1}+X_1O_{n-m,1}-x_1\\ =\frac{Y_0-X_1}{m-1}O_{n-m,1}-x_1.$$

  • $\begingroup$ Thanks. The system only allows me to award the bounty after 24 hours. $\endgroup$ – Sergio Parreiras Apr 27 '15 at 18:17
  • $\begingroup$ Minor typo? $C$ is missing, it should be $y_1=Cx_0+Dx_1=CA^{-1}y_0+(D-CA^{-1}B)x_1.$ $\endgroup$ – Sergio Parreiras Apr 27 '15 at 18:43
  • $\begingroup$ @SergioParreiras: quite right, thanks. $\endgroup$ – Yves Daoust Apr 27 '15 at 18:56

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.